Approaching the genetic dissection of indirect adventitious organogenesis process in tomato explants. (January 2021) - Sánchez-López, Jorge; Atarés, Alejandro; Jáquez-Gutiérrez, Marybel; Ortiz-Atienza, Ana; Capel, Carmen; Pineda, Benito; García-Sogo, Begoña; Yuste-Lisbona, Fernando J.; Lozano, Rafael; Moreno, Vicente
Highlights: Tomato mutants impaired in adventitious organogenesis were identified. The genes altered in these mutants are key regulators of adventitious organogenesis. Gene altered in tdc-1 plays a specific role in callus growth. Gene altered in tds-1 plays a specific role in adventitious shoot development. Sl MAPKKK17 gene plays an important role in adventitious shoot-bud differentiation. Abstract: The screening of 862 T-DNA lines was carried out to approach the genetic dissection of indirect adventitious organogenesis in tomato. Several mutants defective in different phases of adventitious organogenesis, namely callus growth ( tdc-1 ), bud differentiation ( tdb-1, -2, -3 ) and shoot-bud development ( tds-1 ) were identified and characterized. The alteration of the TDC-1 gene blocked callus proliferation depending on the composition of growth regulators in the culture medium. Calli from tds-1 explants differentiated buds but did not develop normal shoots. Histological analysis showed that their abnormal development is due to failure in the organization of normal adventitious shoot meristems. Interestingly, tdc-1 and tds-1 mutant plants were indistinguishable from WT ones, indicating that the respective altered genes play specific roles in cell proliferation from explant cut zones ( TDC-1 gene) or in the organization of adventitious shoot meristems ( TDS-1 gene). Unlike the previous, plants of the three mutants defective in the differentiation of adventitious shoot-buds ( tdb-1, -2, -3 ) showed multiple changes in vegetative and reproductive traits. Cosegregation analyses revealed the existence of an association between the phenotype of the tdb-3 mutant and a T-DNA insert, which led to the discovery that the SlMAPKKK17 gene is involved in the shoot-bud differentiation process.